The carnivale of curiosities [large type] - Gibbs, Amiee (Thorndike Press large print top shelf., 2023)
"In Victorian London, where traveling sideshows are the very pinnacle of entertainment, there is no more coveted ticket than Ashe and Pretorius' Carnivale of Curiosities. Each performance is a limited engagement, and London's elite boldly dare the dangerous streets of Southwark to witness the Carnivale's astounding assemblage of marvels. For a select few, however, the real show begins behind the curtain. Rumors abound that the show's proprietor, Aurelius Ashe, is more than an average magician. It's said that for the right price, he can make any wish come true. No one knows the truth of this claim better than Lucien the Lucifer, the Carnivale's star attraction. Born with the ability to create fire, he's dazzled spectators since he was a boy. When Odilon Rose, one of the most notorious men in London, comes calling with a proposition regarding his young and beautiful charge, Charlotte, Ashe is tempted to refuse. After revealing, however, that Rose holds a secret that threatens the security of the troupe's most vulnerable members, Ashe has no choice but to sign an insidious contract. The stakes grow higher as Lucien finds himself drawn to Charlotte and her to him, an attraction that spurs a perilous course of events. Grave secrets, recovered horrors, and what it means to be family come to a head in this vividly imagined spectacle--with the lives of all those involved suspended in the balance"--